Problems of the Action of Euthanasia as Part of Human Rights - Febriansyah, Febriansyah (Budapest International Research and Critics University, 2022)
One of the protections for human rights in the Constitution can be seen from the guarantee provided by Article 27 of the 1945 Constitution which states that